(untitled) (The Research of Medical Science Review, 2024)
This studies assesses the seed germination test as a non-invasive, fairly priced technique for heifer pregnancy detection. 16 pregnant and sixteen non-pregnant heifers from Jam Nawaz Ali's Katohar Dairy Farm were selected at random for the study. Dilution ratios (1:6 and 1:16) with barley (Hordeum vulgare) and sorghum (Sorghum bicolor) seeds have been used to acquire and examine urine samples. The findings showed that the urine of pregnant heifers extensively suppressed each seed types' germination and shortened branch length (0.05), with barley exhibiting extra constant suppression during the route of the pregnancy. The urine study, which revealed sizable variations in ph, protein content, and color among the pregnant and non-pregnant heifers (16 pregnant and 16 non pregnant), further showed the approach's viability. The effects indicate that the seed germination test, particularly while paired with a urinalysis, may show to be an powerful diagnostic tool for cow pregnancy, offering small-scale farmers an affordable, seven- hundred rupees opportunity. For a wider range of livestock management applications, further research is vital to improve and verify the method across many cattle breeds and different livestock species